Hybrid ceramic as an alternative material for crown restoration treatment - Justin, Alexander; Syafrinani; Putri WU. Ritonga (Indonesian Journal of Prosthodontic, 2025)
Background: All ceramic materials are often used in crown restorations for anterior and/or posterior teeth due to their aesthetic value and high strength. However, some all-ceramic materials such as monolithic zirconia have the disadvantage that they can cause wear problems on antagonistic teeth due to their high hardness. As an alternative to overcome this problem, hybrid ceramic materials are being developed. Objectives: This literature review aims to look at using hybrid ceramic materials as an alternative material for making crowns. A hybrid ceramic material blends the characteristics of ceramic and composite materials, resulting in a material with excellent mechanical strength and aesthetic qualities. It has a similar elastic modulus value to dentin thus reducing the occurrence of wear on antagonistic teeth. Hybrid ceramic materials is fabricated by CAD/CAM system with subtractive (milling) and additive (3D printing) processes. The subtractive fabrication method (milling) produces restorations with high strength properties but has a longer and more complicated manufacturing process. The additive (3D printing) method, on the other hand, is faster and requires less material than subtractive (milling). Summary: Therefore, hybrid ceramic materials should be considered as an alternative material for crown restorations. Keywords: Hybrid ceramic; CAD/CAM; additive (3D printing); subtractive (milling)